Follow-up of patients with uncontrolled asthma: clinical features of asthma patients according to the level of control achieved (the COAS study). Issue 3 (2nd March 2017) - Munoz-Cano, Rosa; Torrego, Alfons; Bartra, Joan; Sanchez-Lopez, Jaime; Palomino, Rosa; Picado, Cesar; Valero, Antonio
Our aim was to study the asthma control achieved in patients with uncontrolled asthma who had received appropriate treatment according to the Global Initiative for Asthma (GINA) 2010 (valid at the time the study was designed), and to analyse the factors associated with a lack of asthma control. This was a multicentre study in routine clinical practice performed in patients with uncontrolled asthma according to GINA 2010. At visit 1, we recorded demographics, asthma characteristics and spirometry. We assessed asthma control using GINA 2010 criteria and the Asthma Control Test (ACT). Treatment was optimised according to GINA 2010. At visit 2, 3 months later, we reassessed spirometry, asthma control and factors associated with failure to achieve control. We recruited 1299 patients with uncontrolled asthma (mean age 46.5±17.3 years, 60.7% women, 25.8% obese). The mean percentage of predicted forced expiratory volume in 1 s was 76.4±12.8% and the mean post-bronchodilator increase was 14.9±6.8%. We observed poor agreement between ACT and GINA 2010 when evaluating asthma control (kappa = −0.151). At visit 2, asthma in 71.2% of patients was still not fully controlled. Patients whose asthma remained uncontrolled were older, had a higher body mass index, greater disease severity, longer disease evolution and worse lung function. After treatment optimisation, most patients did not achieve optimal control according to GINA 2010. Risk factors for failure to achieve asthma control were time of disease evolution, severity, age, weight and lung function impairment (excluded in the GINA 2014). Asthma in most patients is not fully controlled despite adjusting their treatment using GINA 2010 strategy criteria http://ow.ly/C73c307fMOZ